Aquesta nafra gloriosa és botiga d'especieria: La contemplación de la Pasión en la Vita Christi de Isabel de Villena. - PEIRATS, ANNA (Scripta)
This study explores the contemplative narrative surrounding the lifeless body of Christ in medieval texts, based on the influence of Ubertino de Casale's Arbor vitae crucifixae Iesu Christi (AVCJ) on Francesc Eiximenis' and Isabella de Villena's Vita Christi. The article examines variations in stylistic elements, metaphors, and thematic nuances through a comparative analysis of specific chapters of Isabel de Villena's Vita Christi (chapters 144, 219, and 220). This analysis reveals Ubertino's impact on the frankness of Eiximenis's narrative and the amplification of the tone of lamentation in Isabel de Villena, which introduces unique isotopies, portraying Christ's chest as a healing cupboard. The study concludes by highlighting the widespread influence of Ubertino on European spirituality, especially in the Iberian Peninsula, giving shape to the contemplative expressions found in the vitae of Eiximenis and Isabel de Villena.